Pengembangan Virtual Classroom Berbasis Web Learning Pada Mata Pelajaran Bahasa Inggris Untuk Siswa Kelas VII - Amri, Maliki; Setyosari, Punaji; Ulfa, Saida (Universitas Negeri Malang, 2022)
Web Learning-based Virtual Classroom is a complement and a new learning medium for 8th graders at SMP Negeri 1 Pakis in English Subjects, the subject matter is We got a lot of Histories. Web Learning-based Virtual Classroom is a learning medium that involves student and teacher interactions online that students can use to learn independently. Web Learning-based Virtual Classroom has a how-to guide and has many features that make it easier for students to use it. The purpose of this development is to produce a learning media, and to find out the feasibility of the learning media being developed. The development model used is the Lee & Owens model. Responses were obtained from Media and Material Experts, the development of a Web Learning-based Virtual Classroom for English Subjects received a positive response by material experts and media experts and was suitable for use by students.AbstrakVirtual Classroom berbasis Web Learning menjadi pelengkap dan sebuah media belajar baru bagi siswa kelas 8 di SMP Negeri 1 Pakis dalam mata pelajaran Bahasa Inggris materi We got a lot of Histories. Virtual Classroom berbasis Web Learning adalah media pembelajaran yang melibatkan interaksi siswa dan guru secara online digunakan siswa belajar secara mandiri. Virtual Classroom berbasis Web Learning memiliki panduan cara penggunaan dan punya banyak fitur yang memudahkan siswa saat menggunakannya. Tujuan Pengembangan ini adalah menghasilkan sebuah media pembelajaran, serta mengetahui kelayakan dari media pembelajaran yang dikembangkan. Model pengembangan yang digunakan adalah model Lee & Owens. Tanggapan diperoleh dari Ahli Media dan Ahli Materi, pengembangan Virtual Classroom berbasis Web Learning untuk Mata Pelajaran Bahasa Inggris mendapatkan respon positif oleh ahli materi dan ahli media serta layak digunakan oleh siswa.